First, you h ave to cross multiply
4(x+1)=3(x+2)
Next, you expand the equation.
4x+4=3x+6
Then you subtract 4 from both sides.
4x=3x+6−4
After that, you Simplify 3x+6-43x+6−4 to 3x+23x+2
4x=3x+2
Next, Subtract 3x3x from both sides
4x−3x=2
The last step, you Simplify 4x-3x4x−3x to x
x=2
You can also check your answer to see if it is correct.
1) 4/x+2=3/x+1
2) Let x=2
4/2+2=3/2+1
3) Simplify 2+22+2 to 44
4/4=3/2+1
4) Simplify 2+12+1 to 33
4/4=3/3
5) Cancel 4
1=3/3
6) Cancel 3
1=1
And now you know your answer is correct.